'Grandmother, aren't you going to sing for us?' Current childcare practices and caregivers' perceptions of and receptivity to early childhood development activities in rural Burkina Faso. Issue 2 (29th March 2019) - Hollowell, Jennifer; Dumbaugh, Mari; Belem, Mireille; Kousse, Sylvain; Swigart, Tessa; Korsaga, Chantal; Lankoande, Pokiandi Solange; Lawson, Kokovi Hogban; Hill, Zelee
Abstract : Introduction: Effective stimulation and responsive caregiving during the first 2 years is crucial for children's development. By age 3–4 years, over 40% of children in sub-Saharan Africa fail to meet basic cognitive or socioemotional milestones, but there are limited data on parenting and childcare practices. This study, conducted to inform the design of a mass media intervention, explored practices, perceptions, motivators and obstacles to childhood development-related practices among parents and caregivers of children aged 0–2 years in rural Burkina Faso. Methods: We performed two rounds of six focus groups with 41 informants in two villages, using an adapted version of the Trials of Improved Practices methodology. These first explored beliefs and practices, then introduced participants to the principles and benefits of early childhood development (ECD) and provided illustrative examples of three practices (interactive ways of talking, playing and praising) to try with their children. One week later, further discussions explored participants' experiences and reactions. Data were analysed inductively using thematic content analysis. Results: Existing activities with young children were predominantly instructive with limited responsive interaction and stimulation. Participants were receptive to the practices introduced, noted positive changes in their children when they adopted these practices and found engagement with children personally rewarding. Conclusion: Interactive, stimulating activities with young children did not appear to be widespread in the study area, but caregivers were receptive to information about the importance of early stimulation for children's development. ECD messages should be tailored to the local sociocultural context and consider time limitations.